Establishing the foundation for technology adoption: profiles of military students in the digital age - Luna, Andrea; Ocaña, Mauro; Rodríguez-Moreno, Javier; Ortíz-Colón, Ana María (Frontiers in Psychology, 2025)
Military students are often believed to possess different traits compared to civilian students, e.g., discipline and motivation. Yet, to implement a technology-enhanced learning environment, stakeholders must first address the complexity of student learning in military higher education institutions. Through a mixed-methods approach, we used latent profile analysis of MSLQ scores, complemented by a comprehensive study of academic programs and faculty interviews, to reveal that heterogeneity among military students is not significantly different from that of civilian students. We identified four distinct groups: (1) highly motivated students with strong self-efficacy and learning strategies, (2) students with low self-efficacy and high anxiety, (3) moderately motivated students, and (4) students with inconsistent learning profiles. Our analysis revealed that while the current pedagogical structure aims to balance theoretical, practical, and autonomous learning, it may not effectively meet the needs of all student profiles. However, LMS platforms, military simulators, and other digital tools can serve not only as instructional resources but also as potential catalysts for truly personalized and adaptive military education. Effective military pedagogy in the 21st century must recognize and address the diversity of learning profiles. This includes strengthening self-regulation and cognitive strategies through tailored technological interventions, optimizing digitally enriched hands-on activities, and increasing teacher awareness of motivational and emotional factors. This research offers a concrete roadmap for optimizing military training, positioning technology as a key driver of pedagogical transformation to better prepare future military leaders for the challenges of an ever-evolving world.